2020
DOI: 10.1088/1748-9326/abb396
|View full text |Cite
|
Sign up to set email alerts
|

Urban nature in a time of crisis: recreational use of green space increases during the COVID-19 outbreak in Oslo, Norway

Abstract: The global response to the COVID-19 pandemic has brought with it significant changes to human mobility patterns and working environments. We aimed to explore how social distancing measures affected recreational use of urban green space during the partial lockdown in Oslo, Norway. Mobile tracking data from thousands of recreationists were used to analyze high resolution spatio-temporal changes in activity. We estimated that outdoor recreational activity increased by 291% during lockdown relative to a 3 yr avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
534
10
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(597 citation statements)
references
References 37 publications
44
534
10
9
Order By: Relevance
“…Our study does not provide data for an association between mobility and COVID-19 transmission. Nonetheless, the potential impact of green space on mobility during a pandemic shown in our study and other recent literature [7,31,32] implies the need for future design and planning for green space and open spaces where disease control measures such as physical distancing can be performed during an outbreak [31,44,45]. Our results suggest that different plans for sheltering in place in relation to local built environment at regional levels are required.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Our study does not provide data for an association between mobility and COVID-19 transmission. Nonetheless, the potential impact of green space on mobility during a pandemic shown in our study and other recent literature [7,31,32] implies the need for future design and planning for green space and open spaces where disease control measures such as physical distancing can be performed during an outbreak [31,44,45]. Our results suggest that different plans for sheltering in place in relation to local built environment at regional levels are required.…”
Section: Discussionmentioning
confidence: 56%
“…Given the restrictions on the gathering of people particularly in indoor settings during COVID-19, understanding the use of green space contributes to our understanding of how green space relates to the ability of communities to cope with the stress from quarantine and pandemic, such as by playing a role as an alternative place for physical activity. A recent study in Oslo, Norway found that outdoor physical activity levels increased after the lockdown was implemented, and that the increases were highest in trails with greener and more remote areas [31]. A study conducted in the US found that the reduction in mobility to parks impacted by state-of-emergency declarations was smaller than the mobility reduction for other venues across the states [32].…”
Section: Introductionmentioning
confidence: 99%
“…PAs benefit physical and mental health [45][46][47] by providing people with the opportunity to come closer to nature [48][49][50][51]. In addition, a significant increase in users of outdoor spaces [52] has also been documented during the pandemic that appears to be motivated by people trying to find relatively remote places where they felt safe from the virus.…”
Section: Discussionmentioning
confidence: 99%
“…A second lesson that can be drawn from another observation seems to be that a sudden and sharp change in behavior (and mindset) is possible, driven by new social norms like wearing a mask or keeping social distance. The COVID-19 pandemic may have long lasting consequences in the way we work, where we live, and how we spend our leisure time [36,37].…”
Section: A Change In Behavior Is Possiblementioning
confidence: 99%